FIGHTING AS THE FIRST: A CASE STUDY IN UNDERSTANDING THE STRUGGLES OF FIRST-GENERATION UNIVERSITY STUDENTS IN NORTH CAROLINA - Beasley, Tyler Matthew (East Carolina University, 2019)
The purpose of this work was to understand the struggles that first-generation college students experience during their first year in a college/university setting. For the purposes of this study, I defined "first-generation college students" as those students whose parents have not completed a four-year degree. This thesis examines the many ways in which first-generation college students experience hardships during the first year of their collegiate experience (e.g. financial hardships, emotional strains, overall acclimation process, etc.).
Keywords: First-generation college students; first-gens; sociolog; sociology of higher education; College students--Mental health--North Carolina; College students--North Carolina--Attitudes